THE INFLUENCE OF THE QUALITY ACCOUNTING INFORMATION SYSTEM TO THE QUALITY OF ACCOUNTING INFORMATION - EVIDENCE IN INDONESIA - Puspitawati, Lilis; Anggadini, Sri Dewi (Majalah Ilmiah UNIKOM, 2019)
Managers as stakeholders use accounting strategic management in implementing their business strategy. The essence of strategic management accounting is to create satisfaction for its customers which is known as the concept of value chain analysis. Currently the implementation of strategic management accounting has used information technology known as Accounting Information systems. Accounting Information systems produce Accounting Information that managers use in making strategic decisions in any company. This study used descriptive and verificative methods. Respondents in this study were 60 functional managers SOEs in Bandung Indonesia. Quality data tested by Validity and Reliability test. Statistical tests use structural equation model-PLS. Results of this study is Accounting Information Systems have a significant effect on the of accounting information on SOEs in Bandung City -Indonesia Keywords : Quality of Accounting Information Systems, Quality of Accounting Information, State Owner Enterprises